Risk Assessment Method For Insider Threats In Cyber Security : A Review - Zainal Abidin, Zaheera; Zakaria, Nurul Azma; Hashim, Nurul Akmal; Ahmad, Rabiah; A. Perumal, Puvanasvaran (Science and Information Organization, 2018)
Today’s in manufacturing major challenge is to manage large scale of cybersecurity system,which is potentially exposed to a multitude of threats.The utmost risky threats are insider threats.An insider threat arises when a person authorized to perform certain movements in an organization decides to mishandle the trust and harm the organization.Therefore,to overcome these risks,this study evaluates various risk assessment method to assess the impact of insider threats and analyses the current gaps in risk assessment method.Based on the literature search done manually,we compare four methods which are NIST, FRAP,OCTAVE,and CRAMM.The result of the study shows that the most used by an organization is the NIST method.It is because NIST is a method that combines the involvement between human and system in term of collection data.The significance of this study contributes to developing a new method in analyzing the threats that can be used in any organization.